RNA Folding Methods and Protocols - Waldsich, Christina.; Waldsich, Christina. (Methods in Molecular Biology, 2014)
Focusing on in vitro and intracellular RNA structure formation, RNA Folding: Methods and Protocols provides a comprehensive collection of experimental protocols which are suitable to dissect RNA folding pathways and to characterize the structure of RNA folding intermediates at nucleotide or even atomic resolution. The presented techniques include powerful tools with a long tradition in RNA research as well as more advanced, novel methods, thus the methods span multiple disciplines, including molecular biology, biochemistry, biophysics, and computational biology.  Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Practical and authoritative, RNA Folding: Methods and Protocols serves as a vital reference for researchers attempting to gain insights into the secrets of this astounding macromolecule.